Решите ! 1)5-3x> 11 2): a+3 a-3 36 6 - + ) : a-3 a+3 a^2-9 a-3

samruk1974 samruk1974    2   06.09.2019 01:40    0

Ответы
achreneti21 achreneti21  06.10.2020 20:24
1) переносим всё в одну сторону
-3x>6 
x>-2
2) ( \frac{a^{2} + 9 }{(a-3)(a+3)} - \frac{ a^{2} -9} {(a-3)(a+3)} + \frac{36}{ a^{2}-9 } ) : \frac{6}{a-3} =
( \frac{a^{2} + 9 }{a^{2}-9} - \frac{ a^{2} -9} {a^{2}-9} + \frac{36}{ a^{2}-9 } ) : \frac{6}{a-3} =
\frac{36}{ a^{2}-9 } : \frac{6}{a-3} = \frac{36}{ a^{2}-9 }* \frac{(a-3)}{6} =
Сокращаем
\frac{36}{ (a-3)(a+3) }* \frac{(a-3)}{6} = \frac{6}{a+3}
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика